Vitamin B12 Excretion in Patients with Various Skin Diseases. Issue 5723 (12th September 1970) - Marks, Janet; Shuster, Sam
Abstract : The excretion in the urine of 58 Co after an oral dose of 58 Co vitamin B12 given together with intrinsic factor has been found to be reduced in a number of patients with psoriasis, eczema, and other less common dermatoses. There is a correlation between the abnormality and the extent of the rash. A reduced glomerular filtration rate was found in a few of the patients in whom it was measured, and this must have been responsible, at least in part, for the reduced excretion of vitamin B12 in these patients, but abnormal vitamin B12 excretion also occurred in the absence of impaired renal function. Our evidence is insufficient to show whether malabsorption or increased tissue utilization of vitamin B12 was the explanation in other cases. Certainly a number of patients had steatorrhoea, and in these it is most likely that malabsorption was the major factor. In patients without steatorrhoea a lone malabsorption of vitamin B12 cannot be excluded. A decreased serum concentration of vitamin B12 was found in only one of the patients.